1909թ. Ադանայի և Հալեպի Վիլայեթներում տեղի ունեցած կոտորածների ժողովրդական հետևանքները - Բաբլումյան, Արփինե (ՀՀ ԳԱԱ Հայոց ցեղասպանության թանգարան-ինստիտուտ)
The article reveals the main features of population changes after Cilician massacres of 1909. After these massacres the number of Armenian population in the provinces of Adana and Aleppo decreased drastically.
Keywords: Հայոց ցեղասպանություն; Հայոց պատմություն